Understanding Vision Rehabilitation: A Perspective from People with Low Vision - Oviedo-Cáceres, María del Pilar; Hernández-Padilla, Martha Liliana; Suárez-Escudero, Juan Camilo (Revista Cuidarte, 2020)
Introduction: Low vision is a category of visual impairment that needs a rehabilitation process to maximize visual function and provide the individual with compensatory skills to improve their functioning. Objective: To describe the perception of people with low vision who received functional vision rehabilitation in two rehabilitation centers in relation to service provision and barriers identified in the process. Materials and Methods: A qualitative exploratory study was conducted using 14 semi-structured interviews in people who received low vision rehabilitation in two rehabilitation centers: one in Bogotá providing interdisciplinary vision rehabilitation and another in Bucaramanga with less interdisciplinary vision rehabilitation. After analysis, data were recovered, classified and transformed. Results: People who attended the less interdisciplinary rehabilitation center recognized the contribution of rehabilitation for basic and instrumental activities of daily living. Those who attended the rehabilitation center providing greater interdisciplinary vision rehabilitation highlighted the contributions made from the psychology, orientation and mobility skills, and social work fields as essential. Despite this, barriers still exist in both cities: difficulties in acquiring optical, mobility and architectural aids, as well as in labor inclusion. Discussion: There is a clear need to ensure interdisciplinary vision rehabilitation that includes additional interventions for optical aid prescription. Conclusion: Best results are obtained by interdisciplinary vision rehabilitation in terms of transformations that individuals achieve in acceptance of the low vision condition, mobility, access to technology and rights recognition.How to  cite this article: Oviedo-Cáceres María del Pilar, Hernández-Padilla Martha Liliana, Suárez-Escudero Juan Camilo. Percepción de la rehabilitación visual:  Una mirada desde las personas con baja visión. Revista Cuidarte. 2021;12(1):e1139. http://dx.doi.org/10.15649/cuidarte.1139
Keywords: Vision, Low; Rehabilitation Services; Rehabilitation Research, Treatment Outcome; Rehabilitation Research; Health Services for Persons with Disabilities